AN ANALYSIS OF THE CONCEPT OF TAZKIYAH AL-NAFS IN THE QUR’ANIC TAFSIR AND THE BOOK MI‘RĀJ AL-SA‘ĀDAH BY AḤMAD AL-NARĀQĪ - Muhammad Dzikri Abdilah; Riko Reinaldi; Mutiara MY (Sekolah Tinggi Agama Islam Sadra, 2025)
The concept of tazkiyah al-nafs (purification of the soul) holds an important position in the Islamic tradition as it serves as the key to human spiritual and psychological development. Without purification of the soul, it is difficult for a person to achieve holistic growth, both in the inner dimension (faith and peace of heart) and in the dimension of personality (mind, morals, and character). Therefore, the study of tazkiyah al-nafs is highly relevant in efforts to understand the comprehensive formation of human personality. This research aims to examine the concept of tazkiyah al-nafs from the perspective of Qur’anic exegesis as well as the ethical-sufi thought presented in Mi‘rāj al-Sa‘ādah by Aḥmad al-Narāqī. The method employed is qualitative with a library research approach, utilizing primary sources including the Qur’an, both classical and contemporary exegesis, and al-Narāqī’s work. The findings indicate that tazkiyah al-nafs is an internal process of cleansing the soul from blameworthy traits and adorning it with noble character. The Qur’an repeatedly emphasizes this concept, as in Q.S. Ash-Shams [91]: 9–10, which highlights the success of the purified soul. Meanwhile, in Mi‘rāj al-Sa‘ādah, al-Narāqī elaborates the stages of tazkiyah through self-knowledge, mujāhadah (striving), riyāḍah (discipline), and murāqabah (self-vigilance), while also stressing the importance of reason and the sharia as means of purification. The implications of this study show that tazkiyah al-nafs is highly relevant to the development of Islamic psychology, particularly in formulating spiritual therapy and character education based on turāth values. Furthermore, the study opens opportunities for integrating classical Islamic concepts into contemporary psychology, focusing on a balanced approach to both the spiritual and mental dimensions of the individual.